Predictors of survival among breast cancer patients in Ethiopia: a systematic review and meta-analysis - Mulugeta, Chalie; Emagneneh, Tadele; Kumie, Getinet; Ejigu, Betelhem; Alamrew, Abebaw (Frontiers in Oncology, 2025)
IntroductionBreast cancer remains a significant public health issue, with delayed medical attention often leading to advanced stages and poorer survival rates. In East Africa, evidence on the prevalence and factors contributing to the delayed presentation of breast cancer is limited. As a result, this study aims to assess the pooled prevalence of delayed breast cancer presentation and identify contributing factors in East Africa.MethodsWe conducted a systematic review of observational studies from East Africa using PubMed, Google Scholar, Embase, Cochrane Library, Hinari, and Mednar databases. The Newcastle Ottawa 2016 Critical Appraisal Checklist assessed methodological quality. Publication bias was evaluated using a funnel plot and Egger’s test, and heterogeneity was examined with the I-squared test. Data were extracted with Microsoft Excel and analyzed using Stata 11.ResultsThe pooled prevalence of delayed presentation among breast cancer patients in East Africa was 61.85% (95% confidence interval, 48.83%–74.88%). Significant factors contributing to delayed presentation included visiting traditional healers (adjusted odds ratio, 3.52; 95% CI, 1.43–5.59), low educational levels (adjusted odds ratio, 3.61; 95% CI, 2.39–4.82), age > 40 years (adjusted odds ratio, 1.87; 1.03, 2.71), absence of breast pain (adjusted odds ratio, 2.42; 1.09, 3.74), distance >5 km away from home to health institution (adjusted odds ratio, 2.89; 1.54, 4.24), and rural residence (adjusted odds ratio, 3.33; 95% CI, 2.16–4.49).ConclusionThis meta-analysis’ findings demonstrated that over half of breast cancer patients in East Africa delayed detection. Significant factors associated with delayed presentation include age over 40 years, illiteracy, rural residence, use of traditional healers, distance >5 km from a health facility, and absence of breast pain. Healthcare stakeholders and policymakers must be focused on raising awareness and educating people to encourage early detection and prompt therapy.